Beware the woman : a novel [large type] - Abbott, Megan, 1971- (Random House Large Print, 2023)
'Honey, I just want you to have everything you ever wanted.' That's what Jacy's mum always told her. And Jacy felt like she finally did. Newly married and with a baby on the way, Jacy and her new husband, Jed, embark on their first road trip together to visit his father, Dr Ash, in Michigan's far-flung Upper Peninsula. The moment they arrive in the cosy cottage in the lush woods, Jacy feels bathed in love by the warm and hospitable Dr Ash, if less so by his house manager, the enigmatic Mrs Brandt. But their first days take a turn when Jacy has a health scare. Swiftly, vacation activities are scrapped, and all eyes are on Jacy's condition. At the same time, whispers about Jed's long-dead mother and complicated family history seem eerily to be impeding upon the present. As the days pass, Jacy begins to feel trapped in the cottage, her every move surveilled, her body under the looking glass. But are her fears founded or is it paranoia, or cabin fever, or--as is suggested to her--a stubborn refusal to take necessary precautions? The dense woods surrounding the cottage are full of dangers, but are the greater ones inside?